PENERAPAN CHANGE, COMPETITOR, CUSTOMERS , COMPANY PADA PT WADJA INTI MULIA DITINJAU DARI PERESPEKTIF PEMASARAN SYARIAH - Kusuma, Ahmad Arul Ade; Aini, Saqofa Nabilah (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the 4-C Diamond strategy at PT Wadja Inti Mulia in terms of sharia marketing perspective. The main focus of this research is how the Change, Competitor, Customers, Company applied by PT Wadja Inti Mulia is inaccordance with the trading method of the Prophet Muhammad SAW (siddiq,amanah, fathanah, tabligh). The method used in this research is a qualitative approach, by conducting interviews and observations. To test the validity of the data, researchers used source triangulation techniques which will then be drawn conclusions. The results of this study indicate that the 4C-Diamond strategy implemented by PT Wadja Inti Mulia is appropriate in the perspective of Islamic economics, namely based on the way of trading the Prophet Muhammad SAW. Change and competitors, in accordance with the prophet's traits of siddiq andfathanah who implement marketing activities honestly and compete fairly and intelligently in decision making and conduct regular market research. Customer and company, in accordance with the nature of the prophet, namely amanah and tabligh, where the company is highly trusted by consumers and conveys productswell and clearly both within company management and to consumers.